Characterization of epibionts associated with gastropod shells inhabited by Isocheles sawayai (Crustacea: Decapoda: Anomura) on the north coast of Santa Catarina - Gilson Stanski; Alexandre Ribeiro-da Silva; Antonio Leão-Castilho (Revista Mexicana de Biodiversidad)
This study analyzed the taxa associated as epibionts with mollusc shells inhabited by the hermit crab Isocheles sawayai, in order to understand how they affect host crabs. A total of 575 individuals were collected, including 156 females, 103 ovigerous females, and 316 males, which occupied shells of 10 species of gastropods. The epibionts recorded in the shells of I. sawayai belonged to Cirripedia, Polychaeta, Bivalvia, Anthozoa, Demosponge, and Bryozoa. A larger percentage of infestation occurred inside the shell, which may be harmful to the hermit crab because it reduces the internal volume. Ovigerous females used shells with a smaller percentage of infestation (40%), which may be related to the need for more space for the position and development of fertilized eggs. However, a higher proportion of anemones was found in shells used by ovigerous females. The advantage of this association for the anemones and crabs is discussed. The results suggest that shells occupied by epibionts can be a favorable factor for hermit crab survival, mainly for ovigerous females.